Plasma exosomal IRAK1 can be a potential biomarker for predicting the treatment response to renin-angiotensin system inhibitors in patients with IgA nephropathy - Wu, Jianping; Wei, Xiaona; Li, Jiajia; Gan, Yangang; Zhang, Rui; Han, Qianqian; Liang, Peifen; Zeng, Yuchun; Yang, Qiongqiong (Frontiers in Immunology, 2022)
Background: Renin-angiotensin system inhibitors (RASi) are the first choice and basic therapy for the treatment of IgA nephropathy (IgAN) with proteinuria. But about 40% of patients have no response with RASi treatment. The aim of this study was to screening of potential biomarkers for predicting the treatment response of RASi with IgAN. Methods: We included IgAN who were treatment-naive. They received supportive treatment including maximum tolerant dose of RASi treatment for 3 months. According to the degree of decrease in proteinuria after 3 months follow-up, these patients were divided into sensitive group and resistance group. The plasma of the two groups of patients were collected and the exosomes were extracted for high-throughput sequencing. The screening of hub genes was using weighted gene co-expression network (WGCNA) and filter differentially expressed genes (DEGs). We randomly selected 20 patients in the sensitive group and 20 patients in the resistance group for hub genes validation by real-time quantitative polymerase chain reaction (qRT-PCR). A receiver operating characteristic (ROC) curve was used for evaluating the hub genes’ predicting efficacy of RASi response among the 40 validation patients. Results: After screening 370 IgAN patients according to the inclusion and exclusion criteria and the RASi treatment response evaluation, there were 38 patients in the sensitive group and 32 patients in the resistance group. IRAK1, ABCD1 and PLXNB3 were identified as hub genes by analyzing the high-throughput sequencing of the plasma exosomes of the two groups through WGCNA and DEGs. The sequencing data was consistent with the validation data that those three hub genes were up-regulated in resistance group compared with sensitive group. The ROC curve indicated that IRAK1 was good indicators for predicting the therapeutic response of RASi in patients with IgAN. Conclusions: Plasma exosome IRAK1 can be a potential biomarker for predicting the treatment response of RASi in patients with IgAN.